PENDIDIKAN NILAI SIKAP KURIKULUM 2013 DALAM TEMBANG MACAPAT - Fajar Adinugraha; Adisti Ratnapuri (Jurnal Selaras : Kajian Bimbingan dan Konseling serta Psikologi Pendidikan, 2018)
Curriculum 2013 is a curriculum that emphasizes affective aspects (attitude values), cognitive aspects (knowledge), and psychomotor aspects (skill). The affective aspect consists of social values and spiritual values. Before the curriculum 2013 was declared, the Java community already has a life guide in the form of local wisdom called tembang macapat. Tembang macapat is a Javanese literature that belongs to a new Javanese literature. There is a poem containing the worthy value inside the tembang macapat. The worthy value is the social and spiritual value in daily life. Social values consits of honesty , discipline, responsibility, tolerance, cooperation, polite, and confidence. The Spiritual values are found in the tembang macapat which always reminds people to the God. There are 4 (four) types of tembang macapat which are analyzed. They are Pocung, Pangkur, Dhandhanggula and Kinanthi. There are value which found in that songs (tembang). The values are honest, discipline, responsibility, tolerance, polite, confidence and spiritual value. The preservation of the tembang macapat may be used to improve morale in a society that has begun to fade due to cultural influences from outside the Java community. Keywords: curriculum 2013, macapat, social value, spiritual value